Intravenous immunoglobulin in neurological disease: a specialist review. - Wiles, C; Brown, P; Chapel, H; Guerrini, R; Hughes, R; Martin, T; McCrone, P; Newsom-Davis, J; Palace, J; Rees, J; Rose, MR; Scolding, N; et al. (2002)
Treatment of neurological disorders with intravenous immunoglobulin (IVIg) is an increasing feature of our practice for an expanding range of indications. For some there is evidence of benefit from randomised controlled trials, whereas for others evidence is anecdotal. The relative rarity of some of the disorders means that good randomised control trials will be difficult to deliver. Meanwhile, the treatment is costly and pressure to "do something" in often distressing disorders considerable. This review follows a 1 day meeting of the authors in November 2000 and examines current evidence for the use of IVIg in neurological conditions and comments on mechanisms of action, delivery, safety and tolerability, and health economic issues. Evidence of efficacy has been classified into levels for healthcare interventions (tables 1 and 2).